2001
DOI: 10.3171/jns.2001.94.2.0217
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid leak after acoustic neuroma surgery: influence of tumor size and surgical approach on incidence and response to treatment

Abstract: The rate of CSF leakage after TL and RS procedures has remained stable. Factors influencing its occurrence include tumor size but not surgical approach. The TL-related leaks had a significantly higher surgical repair rate than RS-related leaks, an additional factor to consider when choosing an approach. The problem of CSF leakage becomes increasingly important as nonsurgical treatments for acoustic neuroma are developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
85
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(91 citation statements)
references
References 22 publications
4
85
2
Order By: Relevance
“…Overall, our CSF leak rate for all surgical approaches was 10.3% and within range of published rates of 6% to 11%. [7][8][9][10][11][12] We report that CSF leak incidence with preoperative LD placement is not significantly lower than without LD use. Our patient population was unique as most patients had an LD placed prior to surgery compared to those who had not.…”
Section: Discussionmentioning
confidence: 85%
“…Overall, our CSF leak rate for all surgical approaches was 10.3% and within range of published rates of 6% to 11%. [7][8][9][10][11][12] We report that CSF leak incidence with preoperative LD placement is not significantly lower than without LD use. Our patient population was unique as most patients had an LD placed prior to surgery compared to those who had not.…”
Section: Discussionmentioning
confidence: 85%
“…Whereas factors such as age, sex, and tumor size did not correlate with the occurrence of a CSF leak in our series, other studies have reported these factors to be significant. 4,5,11,20 These factors, among others, are fixed variables and, therefore, even if believed to influence the likelihood of a postoperative CSF leak, can only be used to counsel patients with regard to their risk of this complication. The fixed nature of these variables prevents either the surgeon or the patient from altering their effect.…”
Section: Discussion Elevated Bmi As a Risk Factor For A Csf Leakmentioning
confidence: 99%
“…This is in keeping with findings reported by others, 19 although some have not experienced any difference between approaches regarding the leak rates. 3,4 Despite this difference in leak rates in our series, however, we still commonly use the TL approach. We also found a significant association between longer operative times and the development of postoperative CSF leaks.…”
Section: Other Risk Factors For a Csf Leakmentioning
confidence: 99%
“…These findings are consistent with a large body of experience describing CSF leak rates following infratentorial procedures of 8%-17%. 5,9,10,16 Infratentorial surgery predisposes a patient to CSF leak because the hydrostatic pressure of the fluid column places additional stress upon the suture line. The association between prolonged postoperative steroid duration and CSF leak likely comes from the immunosuppressive properties of corticosteroids that can interfere with normal wound healing.…”
Section: Discussionmentioning
confidence: 99%